HUNIAN PALIATIF YANG BERKUALITAS DI LINGKUNGAN RUMAH SAKIT DHARMAIS - Vanessa Maria Liemdra; Himaladin Himaladin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Dharmais Cancer Hospital is surrounded by many residences that have been converted into temporary shelters that do not meet standards and an environment that does not support the needs of its residents, most of whom are cancer survivors. However, a place to live is urgently needed by cancer patients at Dharmais Cancer Hospital because many are undergoing long-term treatment and are from out of town. To get the relationship between the role of the environment and emotional problems of cancer sufferers through architecture, data collection was carried out using qualitative methods. Therefore, through everydayness design methods and healing environments, palliative housing projects can be produced. This project aims to provide an ideal resting space for cancer patients by presenting a functional space within the elongated core to support the treatment process and accommodate emotional issues from an architectural point of view. The function presented also aims to provide support to the patient's family so that the patient has a quality end of life and is psychologically and spiritually ready. Keywords: cancer; healing architecture; palliative; residence Abstrak Rumah Sakit Kanker Dharmais dikelilingi banyak hunian yang dialihfungsikan menjadi rumah singgah sementara yang tidak memenuhi standar dan lingkungan yang kurang mendukung kebutuhan penghuni yang kebanyakan adalah para penderita kanker. Akan tetapi hunian sangat dibutuhkan oleh pasien penderita kanker Rumah Sakit Kanker Dharmais karena banyak yang menjalani pengobatan jangka panjang dan berasal dari luar kota.  Untuk mendapatkan keterhubungan peran lingkungan dan masalah emosional penderita kanker melalui arsitektur dilakukan pengumpulan data dengan metode kualitatif. Maka dari itu, keseharian dan healing environment dapat dihasilkan proyek hunian paliatif. Proyek ini bertujuan untuk menghadirkan ruang beristirahat yang ideal bagi para pasien kanker dengan menghadirkan fungsi – fungsi ruang di dalam core memanjang untuk mendukung proses perawatan dan mewadahi permasalah emosional dari sudut arsitektur. Fungsi yang juga dihadirkan bertujuan untuk memberikan dukungan bagi keluarga pasien sehingga penderita akan memiliki akhir hidup yang berkualitas dan siap secara psikologis dan spiritual.